Characterization of thermal, mechanical and hydration properties of novel films based on Saccharomyces cerevisiae biomass - Delgado, Juan Francisco (2018)
Characterization of films made of Saccharomyces cerevisiae biomass was performed so as to better understand their properties. The treated yeast biomass, named HTH, was prepared by subsequent steps including a first homogenization, heat treatment and final homogenization. Glycerol was added as plasticizer and films were evaluated using different techniques to measure mechanical behaviour, thermal properties and water sorption. Temperature of maximum decomposition rate was found near 300 °C, while the gradually disappearance of amide II band (1543 cm−1) occurred from 225 °C, identified by FTIR spectra of residues of thermally treated films by TGA. A glass transition at 64.5 ± 3.0 °C and two low energy endotherms at 61.2 ± 2.3 and 106.1 ± 0.7 °C were determined in completely dehydrated films without glycerol. When glycerol content was increased the glass transition temperature was shifted to lower values, a maximum elongation of 12% was reached, Young's modulus decreased from 88 to 9 MPa and the water uptake of films raised from 0.49 to 0.79 g H2O/g of dry matter. The characterization of yeast biodegradable films provided evidence of their properties for a potential future use in packaging industry. Industrial relevance: The development of biodegradable films based on yeast biomass carries many advantages to the food industry, such as, the possibility of using commercial pressed baker's yeast or an industrial residue from brewing industry, the use of a low-cost sources and the application of environmentally friendly procedures. The methodologies applied for the development of the film forming dispersion, high pressure homogenization and thermal treatment, are able to be scaled-up to an industrial level.